2018
DOI: 10.1002/aqc.2878
|View full text |Cite
|
Sign up to set email alerts
|

River damming drives population fragmentation and habitat loss of the threatened Danube streber (Zingel streber): Implications for conservation

Abstract: 1. The Danube streber, Zingel streber, is a threatened and data-deficient percid fish endemic to the Danube catchment. The study provides the first data on distribution, life history, and genetic structure of the species at the upstream limit of its historic distribution (south-western Germany). A 3-year surveyeffort with 143 fishing events identified several small, fragmentary populations covering only 7% of the historical range of the species. Census population sizes (N c ) of these subpopulations were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
(51 reference statements)
2
12
0
Order By: Relevance
“…Of the examined species the barbel and the Danube streber showed the highest affinity to pebble and boulder covered, high velocity areas. This finding is consistent with former results about the habitat preference of these species from smaller rivers (Brinker et al, 2018;Er} os, 2007; Gutmann Roberts, Baši c, Britton, Rice, &…”
Section: Discussionsupporting
confidence: 92%
“…Of the examined species the barbel and the Danube streber showed the highest affinity to pebble and boulder covered, high velocity areas. This finding is consistent with former results about the habitat preference of these species from smaller rivers (Brinker et al, 2018;Er} os, 2007; Gutmann Roberts, Baši c, Britton, Rice, &…”
Section: Discussionsupporting
confidence: 92%
“…The Danube streber, on the other hand, is a strictly protected endemic species in Hungary, which is also listed in the Habitat Directive of the European Union (NATURA 2000 species). Although detailed information about the habitat use of the species is limited, the species shows strict preference to medium and large fast‐flowing rivers (Brinker et al, ). In fact, no studies to date examined the offshore habitat use of these species in very large rivers and quantified abundance physical habitat relationships in offshore areas.…”
Section: Methodsmentioning
confidence: 99%
“…Examples include Zingel streber in the Danube River (Germany) (Brinker et al, 2017), Salvelinus confluentus in the Clark Fork River (USA) (Neraas & Spruell, 2001), Percina caprodes in the Cuyahoga River (USA) (Haponski, Marth, & Stepien, 2007), Thymallus thymallus in the Skjern River (Denmark) (Meldgaard, Nielsen, & Loeschcke, 2003), Etheostoma blennioides in the Grand, Thames and Sydenham rivers (Canada) (Beneteau, Mandrak, & Heath, 2009) ,and…”
Section: Discussionmentioning
confidence: 99%
“…Fish population structure driven by the disruptive effect of dams has been described in other species worldwide. Examples include Zingel streber in the Danube River (Germany) (Brinker et al, 2017), Salvelinus confluentus in the Clark Fork River (USA) (Neraas & Spruell, 2001), Percina caprodes in the Cuyahoga River (USA) (Haponski, Marth, & Stepien, 2007), Thymallus thymallus in the Skjern River (Denmark) (Meldgaard, Nielsen, & Loeschcke, 2003), Etheostoma blennioides in the Grand, Thames and Sydenham rivers (Canada) (Beneteau, Mandrak, & Heath, 2009) ,and Salmo trutta in the Nive River (France) (Horreo et al, 2011). Interestingly, Dehais, Eudeline, Berrebi, and Argillier (2010) found a pattern similar to that detected in this study: Squalis cephalus from the Durance River in France also showed low but significant F ST values.…”
Section: Discussionmentioning
confidence: 99%